2010
DOI: 10.1177/0022034510363248
|View full text |Cite
|
Sign up to set email alerts
|

Gels Containing MMP Inhibitors Prevent Dental Erosion in situ

Abstract: Matrix metalloproteinase (MMP) inhibition has been shown to reduce dentin caries progression, but its role in dental erosion has not yet been assessed. This study tested the hypothesis that gels containing MMP inhibitors (epigallocatechin gallate-EGCG and chlorhexidine) can prevent dental erosion. Volunteers (n = 10) wore palatal devices containing bovine dentin blocks (n = 10/group) treated for 1 min with EGCG at 10 (EGCG10) or 400 microM (EGCG400), chlorhexidine at 0.012%, F at 1.23% (NaF), and no vehicle (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
107
1
45

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 30 publications
3
107
1
45
Order By: Relevance
“…Pharmacological studies have reported that MMPs activity was reduced by the application of chlorhexidine (CHX) which in turn leads to the arrest of carious lesion 16,17) . Natural products have been used as folk medicine for thousands of years and are promising sources for novel therapeutic agents 18) .…”
Section: Intorductionmentioning
confidence: 99%
“…Pharmacological studies have reported that MMPs activity was reduced by the application of chlorhexidine (CHX) which in turn leads to the arrest of carious lesion 16,17) . Natural products have been used as folk medicine for thousands of years and are promising sources for novel therapeutic agents 18) .…”
Section: Intorductionmentioning
confidence: 99%
“…12 To minimize this process, green tea has a significant inhibitory effect on MMPs and dentin demineralization. 15,16,17 The reduced daily exposure to acid may be minimized by the use of metalloproteinase inhibitors, which protect the organic matrix as a barrier to ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies have demonstrated that the polyphenols contained in certain natural products, such as propolis 8 and green tea, 10,15 may have inhibitory properties against matrix metalloproteinases (MMP) -2 and -9, which could affect the remineralization of artificially demineralized dentin. 10,15 The roots of the Euclea species are rich in naphthoquinones, which may help explain their therapeutic activity, since these compounds have fungicidal, antibacterial, insecticidal, phytotoxic, cytotoxic and anti-carcinogenic properties.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…10,15 The roots of the Euclea species are rich in naphthoquinones, which may help explain their therapeutic activity, since these compounds have fungicidal, antibacterial, insecticidal, phytotoxic, cytotoxic and anti-carcinogenic properties.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation